113k views
4 votes
-3y + 2x = -7
8x - 3y = -1

2 Answers

1 vote

Answer:

x = -4/5

y = 9/5

Explanation:

-3y + 2x = -7

8x - 3y = -1

make one of the equations y=....

-3y + 2x = -7

-3y = -7 - 2x

y = (-7 - 2x)/3

now put (-7 - 2x)/3 where y is in the other equation

8x - 3y = -1

8x - 3((-7 - 2x)/3) = -1

8x - 1*(-7 - 2x) = -1

8x + 7 + 2x = -1

solve for x

8x + 7 + 2x = -1

8x+2x = -8

10x = -8

x = -8/10

x = -4/5

now put -8/10 in one of the equations to get what y is

-3y + 2x = -7

-3y + 2(-8/10) = -7

-3y - 16/10 = -7

-3y = -7 + 16/10

-3y = -70/10 + 16/10

-3y = -54/10

y = -54/10 * -1/3

y = 18/10

y = 9/5

User Nishant Patel
by
6.0k points
3 votes

Answer: If you're solving for the substitution method then your answer would be (1,3)

Explanation:

User Synergetic
by
5.6k points